Subcellular Propagation of Cardiomyocyte β-Adrenergic Activation of Calcium Uptake Involves Internal β-Receptors and AKAP7. Issue 3 (5th May 2022) - Shannon, Thomas R; Bare, Dan J; Van Dijk, Sabine; Raofi, Shayan; Huynh, Tiffany N-M; Xiang, Yang K; Bossuyt, Julie; Dodge-Kafka, Kimberly L; Ginsburg, Kenneth S; Bers, Donald M
Abstract: β-adrenergic receptor (β-AR) signaling in cardiac myocytes is central to cardiac function, but spatiotemporal activation within myocytes is unresolved. In rabbit ventricular myocytes, β-AR agonists or high extracellular [Ca] were applied locally at one end, to measure β-AR signal propagation as Ca−transient (CaT) amplitude and sarcoplasmic reticulum (SR) Ca uptake. High local [Ca]o, increased CaT amplitude under the pipette faster than did ISO, but was also more spatially restricted. Local isoproterenol (ISO) or norepinephrine (NE) increased CaT amplitude and SR Ca uptake, that spread along the myocyte to the unexposed end. Thus, local [Ca]i decline kinetics reflect spatio-temporal progression of β-AR end-effects in myocytes. To test whether intracellular β-ARs contribute to this response, we used β-AR-blockers that are membrane permeant (propranolol) or not (sotalol). Propranolol completely blocked NE-dependent CaT effects. However, blocking surface β-ARs only (sotalol) suppressed only ∼50% of the NE-induced increase in CaT peak and rate of [Ca]i decline, but these changes spread more gradually than NE alone. We also tested whether A-kinase anchoring protein 7γ (AKAP7γ; that interacts with phospholamban) is mobile, such that it might contribute to intracellular spatial propagation of β-AR signaling. We found AKAP7γ to be highly mobile using fluorescence recovery after photobleach of GFP tagged AKAP7γ, and that PKA activation accelerated AKAP7γ-GFP wash-out upon myocyte saponin-permeabilization, suggesting increased AKAP7γ mobility. We conclude that local β-AR activation can activate SR Ca uptake at remote myocyte sites, and that intracellular β-AR and AKAP7γ mobility may play a role in this spread of activation. Graphical Abstract: